Effects of Temperature Treatments on Cytosine-Methylation Profiles of Diploid and Autotetraploid Plants of the Alpine Species Ranunculus kuepferi (Ranunculaceae) - Syngelaki, Eleni; Schinkel, Christoph C. F.; Klatt, Simone; Hörandl, Elvira (Frontiers in Plant Science, 2020)
The exposure to environmental stress can trigger epigenetic variation, which may have several evolutionary consequences. Polyploidy seems to affect the DNA methylation profiles. Nevertheless, it abides unclear whether temperature stress can induce methylations changes in different cytotypes and to what extent a treatment shift is translated to an epigenetic response. A suitable model system for studying these questions is Ranunculus kuepferi, an alpine perennial herb. Diploid and tetraploid individuals of R. kuepferi were exposed to cold [+7°C day/+2°C night; frost treatment: -1°C cold shocks for three nights per week ] and warm [+15° day/+10°C night ] conditions in climate growth chambers for two consecutive flowering periods and shifted from one condition to the other after the first flowering period. Methylation-sensitive amplified fragment-length polymorphism markers were applied for both years, to track down possible alterations induced by the stress treatments. Patterns of methylation suggested that cytotypes differed significantly in their profiles, independent from year of treatment. Likewise, the treatment shift had an impact on both cytotypes, resulting in significantly less epiloci, regardless the shift’s direction. The AMOVAs reflect the DNA methylation dynamics of tetraploids, as a response to temperature’s change, and follow up the hypothesis of cold stress affecting the epigenetic variation. Results suggest that the temperature-sensitivity of DNA methylation patterns shows a highly dynamic phenotypic plasticity in R. kuepferi, as both cytotypes responded to temperature shifts. Furthermore, ploidy level has an important effect on epigenetic background variation, which may be correlated with the DNA methylation dynamics during cold acclimation.